The Effect Of Audit Committee, Gender Commissioners And Directors, Role Duality, And Firm Size Againts Extension Of Sustainability Report Disclosure - Shafrani Dizar; Sarah Alifia; Fithri Alvionita (Universitas Trisakti, 2018)
The purpose of this research is to investigate the effect of audit committee, gender of Commisioners and Directors, role duality, and firm size against extention of sustainability report disclosure. The population of this research comprises companies registered as manufacturing companies which are listed on the Indonesia Stock Exchange for the periods 2015-2017. The technique of determining the sample used is purposive sampling. This research uses a multiple linear regression. This research proves that audit committee, gender of Commissioners and Directors, role duality, and firm size together have an effect against sustainability report disclosure. This research also proves that partially audit committee and firm size have a positive effect against sustainability report disclosure. Meanwhile, gender of Commissioners and Directors doesn’t have positive effect and role duality doesn’t have negative effect against sustainability report disclosure.